Seminal fluid and sexual selection in the Red junglefowl, Gallus gallus - Alvarez-Fernandez, A (2016)
Sexual selection continues after copulation when the ejaculates from different males compete to achieve fertilization. Post-copulatory sexual selection is therefore a powerful evolutionary pressure, with seminal fluid emerging as an important factor. This thesis studies the role of seminal fluid in sexual selection in the polyandrous Red junglefowl, Gallus gallus. First, sperm Average Path Velocity (VAP) in vitro was higher over time when sperm were exposed to non-self, and particularly non-self related, seminal fluid. There was a tendency for sperm exposed to non-self seminal fluid to produce more hydrolysis points on the PVL membrane of the egg than sperm exposed to self seminal fluid. Second, males preferentially invested sperm in sexually novel females, by decreasing investment over successive copulations with the same female and increasing it again on encountering the new female. Seminal fluid volume allocation patterns mirror those of sperm. Seminal fluid protein allocation showed a status-specific pattern. While dominant males tended to allocate a constant amount of seminal fluid protein to successive copulations, subdominant males tended to increase their investment on the novel females. Third, I identified 1,141 proteins in the Red junglefowl seminal fluid, including proteins involved in immunity and antimicrobial defences, sperm maturation, metabolism, and fertilization. These proteins reveal a substantial contribution of blood plasma proteins that is conserved with humans. A comparison with the domestic fowl seminal fluid proteome, revealed qualitative and quantitative differences, likely associated with domestication and artificial selection. Fourth, by comparing the seminal fluid proteome of young and old males with fast and slow sperm velocity, I identified proteins associated with male reproductive ageing and sperm quality. This thesis shows that seminal fluid can play a potentially important role in sexual selection, and provides novel insights regarding male fertility and the molecular basis of reproductive divergence in seminal fluid proteins associated with domestication and artificial selection.